EDUKASI PERILAKU PENCEGAHAN PENYAKIT TUBERKULOSIS DI RS. WOODWARD - Rammang, Sisilia; Revalina, Revalina (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Tuberculosis (TB or TBC) is an infectious disease caused by the germ Mycobacterium tuberculosis. These germs usually enter the human body through breathing air into the lungs, then these germs can spread from the lungs to other parts of the body through the circulatory system, lymphatic system, through the respiratory tract (bronchus) or spread directly to other parts of the body.This community service aims to increase public knowledge and awareness in preventing the transmission of pulmonary tuberculosis. The counseling method uses leaflet media and will be carried out on December 9 2023 at the hospital. Woodward, Palu City. As a result of community service, the material presented was able to increase their knowledge as evidenced by the evaluation session, the community was asked questions and on average the community was able to answer correctly according to the material provided. Conclusion: Community service activities have been carried out. It is hoped that the excellent presence and enthusiasm of the residents can prevent the occurrence of Tuberculosis.